Distribution management in the health club industry: the impact of a company’s image and environment when choosing a point of sale (POS) - Freitas, Mónica Sofia de (2010)
The objective of this investigation is to study how a store’s environment influences consumers when choosing a point of sale (POS). The POS that is taken into account is part of the tertiary industry: Health Clubs. This project is set on identifying the principle characteristics of Health Clubs in Portugal that are taken in consideration when clients or potential clients are considering joining a club of this nature. Store environment, in theory, consists of three factors: ambient, design and service provided by employees, which in this investigation will be identified as the social factor. On the other hand, the store choice criteria that will be analysed are: service quality, price and store image. The research done in this investigation also includes a study on consumer behaviour, in order to comprehend the link between the store environment and the consumers store choice criteria. The conclusions of this project are based on 121 questionnaires which were distributed by means of two channels: the internet (mailing) and physical distribution (personal interview). The target population are the members of a private Health Club situated in Torres Vedras and the respondents were selected by using convenience sampling. This investigation proposes a conceptual model that analyzes the consumer’s perception of the store’s atmospherics and how these influence the consumer’s store choice.